Scale model design for the stiffened plate subjected to combined longitudinal compression and lateral pressure considering collapse modes. (1st January 2022) - Ma, Hongyang; Mei, Hongyuan; Wang, Deyu
Abstract: The similitude criteria of stiffened plates subjected to combined longitudinal compression and lateral pressure are explored based on the collapse modes. The proposed approaches assume the plate, overall, beam-column, web and torsional slenderness would domain the collapse modes. Apart from these ratios, a non-dimensional parameter of lateral pressure is used for designing the magnitude of lateral pressure acting on the scale models for experiments in the laboratory. Meanwhile, the scaling factors of lateral pressure are proposed based on the thin-walled beam theory, which is used to verify the validation of the dimensionless parameter of lateral pressure. The similitude of the full-scale prototype and scale models are verified by the normalized ultimate stress. In view of the numerical results, the similitude criteria could give a reasonable design of scale models under the combined loads. Highlights: (1) The similitude criteria of stiffened plates subjected to combined longitudinal compression and lateral pressure are presented. (2) Four kinds of typical collapse modes (Overall, Beam-column, Tripping and Web) are selected to verify the similitude criteria. (3) The scaling factors of lateral pressure are proposed based on the thin-walled beam theory, which is used to verify the validation of the dimensionless parameter of lateral pressure. (4) The minimum number of stiffened plate unit are explored in the four typical collapse modes, which could maintain the ultimate strength and save space.